2019
DOI: 10.3847/2041-8213/ab1f80
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Transition Alumina Dust around Asymptotic Giant Branch Stars: Condensation Experiments using Induction Thermal Plasma Systems

Abstract: Mid-infrared spectroscopic observations of oxygen-rich asymptotic giant branch (AGB) stars show the common presence of dust species that have a broad feature at ∼11–12 μm. Chemically synthesized amorphous alumina (Al2O3) is widely accepted as the source of this emission, although it is not obvious that amorphous alumina can condense in circumstellar conditions. We performed condensation experiments of Al–Si–Mg–O and Mg–Al–O gases using induction thermal plasma systems, in which small particles condense from va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…The infrared (IR) transmission spectra of the pellets in the wavelength range from 400-7500 cm −1 (1.3-25.0 µm) were measured with a JASCO MFT-680 at Kyoto University. For comparison, we also obtained IR spectra of quartz, amorphous silica (Takigawa et al 2019), amorphous enstatite, and amorphous forsterite (Imai 2012). FE-SEM analysis was performed on a JEOL JSM-7001F equipped with an Oxford Int.…”
Section: Sample Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The infrared (IR) transmission spectra of the pellets in the wavelength range from 400-7500 cm −1 (1.3-25.0 µm) were measured with a JASCO MFT-680 at Kyoto University. For comparison, we also obtained IR spectra of quartz, amorphous silica (Takigawa et al 2019), amorphous enstatite, and amorphous forsterite (Imai 2012). FE-SEM analysis was performed on a JEOL JSM-7001F equipped with an Oxford Int.…”
Section: Sample Analysismentioning
confidence: 99%
“…Synthetic experiments based on the condensation model are generally performed using an induction thermal plasma (ITP) furnace to form GEMS analog particles in order to investigate the formation process and possible origins of GEMS (Tanaka et al 2014;Matsuno et al 2021;Kim et al 2021). The ITP system generates a rapid cooling of gas from high temperatures which simulates the environment in which condensation of cosmic dust occurs (Takigawa et al 2019;Matsuno et al 2021;Kim et al 2021). Matsuno et al (2021) first successfully synthesized textures similar to GEMS, where multiple Fe-metal grains are included in Mg-rich amorphous silicate by using S-free CI and GEMS-mean compositions while systematically changing the redox conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we perform condensation experiments using a simple system of MgO-SiO 2 and a sulfur-free CI chondritic composition to reproduce GEMS-like grains from a gas. The condensates synthesized in the ITP systems can be compared with the circumstellar dust formation conditions by scaling the experimental conditions in the ITP systems (Matsuno et al 2021;Takigawa et al 2019). The condensation conditions of GEMS compared with those of the present experiments are discussed based on nucleation and growth theory from vapor (Yamamoto & Hasegawa 1977;Kozasa & Hasegawa 1987).…”
Section: Introductionmentioning
confidence: 96%
“…Mid-infrared observations show the presence of alumina dust (amorphous Al 2 O 3 ) in the extended envelopes of O-rich AGB stars. Although only recent condensation experiments confirmed that amorphous alumina can condense in circumstellar conditions [5], intermediate mass (IM) AGB stars have been considered to be the main source of alumina dust in the galaxy for many years, starting from the first work by Onaka et al [6], to the most recent ones Dell'Agli et al [7], Ventura et al [8] (and the references therein).…”
Section: Introductionmentioning
confidence: 99%